Modulation of Titin-Based Stiffness in Hypertrophic Cardiomyopathy via Protein Kinase D - Herwig, Melissa; Kolijn, Detmar; Lódi, Mária; Hölper, Soraya; Kovács, Árpád; Papp, Zoltán; Jaquet, Kornelia; Haldenwang, Peter; Dos Remedios, Cris; Reusch, Peter H.; Mügge, Andreas; Krüger, Marcus; et al. (Frontiers in Physiology, 2020)
The giant protein titin performs structure-preserving functions in the sarcomere and is important for the passive stiffness (Fpassive) of cardiomyocytes. Protein kinase D (PKD) enzymes play crucial roles in regulating myocardial contraction, hypertrophy and remodelling. PKD phosphorylates myofilament proteins, but it is not known whether titin is also a PKD substrate. Here, we aimed to determine whether PKD phosphorylates titin and thereby modulates cardiomyocyte Fpassive in normal and failing myocardium. The phosphorylation of titin was assessed in cardiomyocyte-specific PKD knock-out mice (cKO) and human hearts using immunoblotting with a phosphoserine/threonine and a phosphosite-specific titin antibodies. PKD-dependent site-specific titin phosphorylation was quantified in vivo by mass spectrometry using stable isotope labeling by amino acids in cell culture (SILAC) of SILAC-labelled mouse heart protein lysates that were mixed with lysates isolated from hearts of either wild-type control (WT) or cKO mice. Fpassive of single permeabilized cardiomyocytes was recorded before and after PKD and HSP27 administration. All-titin phosphorylation was reduced in cKO compared to WT hearts. Multiple conserved PKD-dependent phosphosites were identified within the Z-disk, A-band and M-band regions of titin by quantitative mass spectrometry, and many PKD-dependent phosphosites detected in the elastic titin I-band region were significantly decreased in cKO. Titin site-specific phosphorylation showed unaltered or upregulated phosphorylation in cKO compared to WT hearts. Fpassive was elevated in cKO compared to WT cardiomyocytes and PKD administration lowered Fpassive of WT and cKO cardiomyocytes. Cardiomyocytes from hypertrophic cardiomyopathy (HCM) patients showed higher Fpassive compared to control hearts and significantly lower Fpassive after PKD treatment. In addition, we found higher phosphorylation at CaMKII-dependent titin sites in HCM compared to control hearts. Expression and phosphorylation of HSP27, a substrate of PKD, were elevated in HCM hearts, which was associated with increased PKD expression and phosphorylation. The relocalization of HSP27 in HCM away from the sarcomeric Z-disk and I-band suggested that HSP27 failed to exert its protective action on titin distensibility. This protection could, however, be restored by administration of HSP27, which significantly reduced Fpassive in HCM cardiomyocytes. These findings establish a previously unknown role for PKDin regulating diastolic passive properties of healthy and diseased hearts.